PENGARUH PENGGUNAAN TLSO (THORACAL LUMBAL SACRAL ORTHOSIS) TERHADAP ALIGMENT VERTEBRAE PADA LANSIA - Cica Tri Mandasari Ningsih; Muhammad Fathi (Poltekkes Kemenkes Jambi, 2022)
Background: The most common changes in the vertebrae include the head leaning forward (cervical kyphosis), an increase in the thoracic kyphosis curve, a flattened lumbar curve (lumbar kyphosis), a decrease in the thickness of the intervertebral discs so that the height decreases. The purpose of this study was to analyze the use of TLSO for vertebral alignment postures in the elderly with Kyphosis Method: using a quasi experimental pre and post test design method. Sampling used a purposive sample with 30 elderly respondents. Each respondent will be given the TLSO intervention, then measured for vertebrae alignment before and after treatment. For data analysis using the Paired Samples T-test. Results: The use of TLSO has an effect on alignment before and after the intervention which is statistically significant (t = 35.98, mean difference = 8.34 and p value = 0.000) Conclusion: The use of TLSO can reduce the alignment curve of the vertebrae and can reduce the risk of falling in the elderly.